PERPUSTAKAAN GAMPONG DAN MINAT BACA BUKU AGAMA PADA MASYARAKAT ACEH - Muliadi Kurdi; Rahmati Rahmati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
A library is a work unit in the form of a place to store collections of library materials that are systematically arranged in a certain way to be used continuously by the user as a source of information. Village library is an inseparable part of the world of education. Villages that have a complete library will be able to develop wider community knowledge. But in reality, the facilities in the village library are inadequate, for example, collection materials such as textbooks, religious books and general information that are only a few or incomplete. The purpose of this study was to determine the effect of the gampong library on the interest in reading religious books for the people in Aceh province. The research design used is a quantitative method, while for the sample in this study are in Aceh Province. The total number of residents to be studied is 300 people. Data collection techniques in this study were observation, interviews, and questionnaires. Based on the results of the study, the results of the Acehnese community on reading religious books available in the gampong library can be said to be very good, this can be seen from the percentage results where the percentage of people's learning interest averages above 60%. Then it can be concluded that there is an influence of the gampong library on the interest in reading religious books for the people in Aceh province.